Box–Behnken designed adsorption based elution – unique separation process for commercially important acetyl shikonin from Arnebia nobilis. Issue 9 (22nd December 2014) - Subramaniam, Shankar; Palanisamy, Anbumathi; Sivasubramanian, Aravind
Abstract : Box–Behnken optimized, adsorption based robust separation technique for acetyl shikonin (AS), a commercially important compound from industrial crop Arnebia nobilis . Abstract : Acetyl shikonin (AS), a pharmaceutically and commercially important compound, is a minor constituent in the industrial crop Arnebia nobilis . A Box–Behnken optimized, robust separation technique for AS was established by an adsorption based elution method. Optimized yields depict an increase of 78.9% total recovery of AS (97.8% pure), compared to conventional chromatography.